Biological synthesis of silver nanoparticles using Rheum ribes and evaluation of their anticarcinogenic and antimicrobial potential: A novel approach in phytonanotechnology - Aygün, Ayşenur; Gülbağça, Fulya; Nas, Mehmet Salih; Alma, Mehmet Hakkı; Çalımlı, Mehmet Harbi; Ustaoglu, Buket; Altunoglu, Yasemin Celik; Baloğlu, Mehmet Cengiz; Cellat, Kemal; Şen, Fatih (Elsevier BV, 2020)
This paper reports the anticarcinogenic and antimicrobial properties of silver nanoparticles (Ag NPs) obtained by green synthesis using the extract of Rheum ribes (R. ribes), a medicinal plant. For the synthesis of Ag NPs, the ethanolic extracts of R. ribes were used as a reducing as well as the stabilizing agent. For the characterization of Ag NPs, advanced analytical methods such as transmission electron microscopy (TEM), X-Ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-vis spectrophotometry were performed. The synthesized Ag NPs obtained from R. ribes were evaluated as a cytotoxic agent against MDA-MB-231 breast carcinoma cell line. The IC50 values of the nanoparticles were ranged from 165 to 99 μg/mL against MDA-MB 231 cell line for 24 h and 48 h, respectively. The results show that the use of Ag NPs at low concentrations show the toxic effect in the cancer cells. In addition, the results of experiments on gram-positive (Staphylococcus aureus (S. aureus), Methicillin-resistant Staphylococcus aureus (MRSA) and Bacillus subtilis (B. subtilis)) and gram-negative (Escherichia coli (E. coli)) bacteria showed that the Ag NPs had high antimicrobial activity. The results suggest that Ag NPs can be developed as potential anticancer and antibacterial agents.
Keywords: Silver; Bacteria; Plant Extracts; Characterization; Metal Nanoparticles; Breast Neoplasms; Antineoplastic Agents, Phytogenic; Anti-Bacterial Agents; Inhibitory Concentration 50; Anticancer; Cell Line, Tumor; Humans; Antimicrobial; Female; Ag nanoparticle; Rheum; Green Synthesis; 3. Good health